2014
DOI: 10.1021/jm4019299
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of 2-[3,5-Dichloro-4-(5-isopropyl-6-oxo-1,6-dihydropyridazin-3-yloxy)phenyl]-3,5-dioxo-2,3,4,5-tetrahydro[1,2,4]triazine-6-carbonitrile (MGL-3196), a Highly Selective Thyroid Hormone Receptor β Agonist in Clinical Trials for the Treatment of Dyslipidemia

Abstract: The beneficial effects of thyroid hormone (TH) on lipid levels are primarily due to its action at the thyroid hormone receptor β (THR-β) in the liver, while adverse effects, including cardiac effects, are mediated by thyroid hormone receptor α (THR-α). A pyridazinone series has been identified that is significantly more THR-β selective than earlier analogues. Optimization of this series by the addition of a cyanoazauracil substituent improved both the potency and selectivity and led to MGL-3196 (53), which is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
88
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 127 publications
(90 citation statements)
references
References 34 publications
1
88
1
Order By: Relevance
“…Resmetirom is an orally active agonist of THR that is liverdirected with a 28-fold more selectivity than triiodothyronine (T3) for THR-β than THR-α [12]. A recent phase 2b trial randomized patients with biopsy-proven NASH to resmetirom (n = 84) or placebo (n = 41) in a 2:1 ratio [13].…”
Section: Resmetirom As a Promising Therapeutic Agentmentioning
confidence: 99%
“…Resmetirom is an orally active agonist of THR that is liverdirected with a 28-fold more selectivity than triiodothyronine (T3) for THR-β than THR-α [12]. A recent phase 2b trial randomized patients with biopsy-proven NASH to resmetirom (n = 84) or placebo (n = 41) in a 2:1 ratio [13].…”
Section: Resmetirom As a Promising Therapeutic Agentmentioning
confidence: 99%
“…More recently, two liver-directed THRB selective agonists, MGL-3196 and VK2809, have been developed [160,161]. Results from phase II trials showed preventive effects on NAFLD accompanied by a decrease in serum levels of LDL cholesterol and triglycerides as well as hepatic lipids with none of the side-effects of the thyroid hormone axis.…”
Section: Potential Application Of Th and Analogs In Nafld And Hccmentioning
confidence: 99%
“…Resmetirom (MGL-3196) is a highly selective thyroid hormone receptor β (THRβ) agonist. 157 THRβ-selective agonism is hypothesised to elicit the beneficial effects on dyslipidaemia without eliciting the adverse effects of thyroid hormone receptor α agonism in heart and bone. In a Phase 1 study, MGL-3196 dosed at 50 mg per day or higher for 2 weeks significantly reduced LDL-C by 30% and showed a trend for decreased TG.…”
Section: Thyroid Hormone Receptor β Agonistmentioning
confidence: 99%